2011
DOI: 10.1007/s10008-011-1566-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimising organic ionic plastic crystal electrolyte for all solid-state and higher than ambient temperature lithium batteries

Abstract: Organic ionic plastic crystal (OIPC) electrolytes are among the key enabling materials for solid-state and higher than ambient temperature lithium batteries. This work overviews some of the parameter studies on the Li|OIPC interface using lithium symmetrical cells as well as the optimisation and performance of Li|OIPC|LiFePO 4 cells. The effects of temperature and electrolyte thickness on the cycle performance of the lithium symmetrical cell, particularly with respect to the interfacial and bulk resistances, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 17 publications
3
62
0
Order By: Relevance
“…[1][2][3][4][5] OIPCs have these unique properties because they can exist in several distinct solid phases at temperatures below the melting point. [1][2][3][4][5] OIPCs have these unique properties because they can exist in several distinct solid phases at temperatures below the melting point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] OIPCs have these unique properties because they can exist in several distinct solid phases at temperatures below the melting point. [1][2][3][4][5] OIPCs have these unique properties because they can exist in several distinct solid phases at temperatures below the melting point.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory electrochemical performance of the materials was reported when soaked with organic carbonate solvents or ionic liquids as electrolytes. We have chosen to study the OIPC N-ethyl-N-methylpyrrolidinium tetrauoroborate [C 2 mpyr][BF 4 ] due to its broad plastic crystal range, and its composites with PVDF electrospun nanobres, with and without the addition of LiBF 4 . 23 Here we sought to combine the benecial effects of OIPCs as highly conductive solid-state electrolytes with the relatively high mechanical strength and chemical durability of polymer nanobres by bringing them together to make composite electrolyte membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, plastic-crystalline electrolytes are ideal for portable batteries because their mechanical flexibility reduces the problem of poor electrical contact with the electrodes caused by thermal volume changes of solid electrolytes, while eliminating the leakage problems associated with liquid electrolytes. 11,12 We study here a plastic crystalline electrolyte based on the small, high-symmetry succinonitrile molecule (SN, C 2 H 4 (CN) 2 ). Near room temperature, SN is well-known to exhibit plasticcrystalline characteristics combined with unusually high ion mobility, a feature that has been exploited in the last decade to achieve high-conductivity solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the impedance spectra of the cell after the first and the third cycles, it was observed that the charge transfer impedance decreased from 800 Ω to 360 Ω after three cycles. The decrease of impedance with increasing cycles might be attributed to the formation of a passivation layer and good contact compatibility between lithium and the solid-state electrolyte interface (Sunarso et al, 2012), which could be the reason for the capacity increase during the first three cycles.…”
Section: Cell Testsmentioning
confidence: 99%
“…Shekibi et al (2012) exhibited viable ionic conductivity at the level of 10 −3 S/cm at 100 °C, and the discharge capacity in LiFePO 4 /Li cell was about 100 mA·h/g at 80 °C with current density of C/10. Sunarso et al (2012) Organosilicon-based materials have attracted great attention as electrolytes for electrochemical energy storage devices due to their excellent thermal stability, viable ionic conductivity at low temperatures, low flammability, high electrochemical stability, and environmentally benign characters (Shirota and Castner, 2005;Zhang et al, 2008;Rossi and West, 2009;Weng et al, 2011). We have been dedicated to the design and synthesis of organosiliconbased electrolytes, including liquid electrolytes and ionic liquids, for applications in electrochemical energy storage devices such as lithium-ion batteries and supercapacitors (Zhong et al, 2012;Qin et al, 2013;Yan and Zhang, 2013;Yong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%